A new tiger beetle species (Coleoptera, Adephaga, Cicindelidae) from mid-Cretaceous Kachin amber of northern Myanmar - Xia, Qihao; Jarzembowski, Edmund A.; Xiao, Chuantao; Cheng, Hao; Song, Zhenyu (Zootaxa, 2026)
Fossil tiger beetles are scarce. Here we describe a new tiger beetle species, Hujia gongi sp. nov., from mid-Cretaceous Kachin amber. The new specimen is attributable to the family Cicindelidae due to sickle-shaped mandibles, elongated prothorax, slender ambulatory legs and the ratios of BW: TL and IL: TL. It is the second species of the genus from the same location that can be distinguished from its congener by its larger size, slightly forward-tapering head and broadened tarsomeres of the prothoracic leg, demonstrating male characteristics and potentially greater predation ability. The new taxon represents the fourth definite Mesozoic record of Cicindelidae.